(untitled) (Vietnam Journal of Community Medicine, 2022)
Purpose: To evaluate the early effectiveness of Ahmed valve glaucoma for refractory glaucoma following pars plana vitrectomy. Methods: Noncomparative interventional case series. In this study, we analyzed the medical records of patients at Ho Chi Minh Eye Hospital, from July 2019 to February 2020. All patients suffering from secondary glaucoma following pas plana vitrectomy and IOP could not be controlled with maximum anti-glaucoma drugs (3 agents) for at least 2 weeks were implemented with Ahmed glaucoma valve implantation. Patients were evaluated at 1 day, 1 month, 3 months, 6 months and each 3 months post-operatively until the end of study. Results: Thirty-four eyes of 33 patients with a mean age of 46.71 ± 14.40 years underwent a AGV implantation. The average follow-up after surgery was 11.49 ± 4.99 months (range 6-24 months). On average, treatment reduced the IOP by 15.4 ± 7.4 mmHg at the last visit. Kaplan–Meier survival analysis revealed cumulative success of 97.1% at 3 months, 94.1% at 4 months, 91.2% at 6 months, 87.5% at 9 months and still stable until 24 months. Vision-threatening complications did not recorded. The success rate was 88,23%. Cause of failure was high IOP due to bleb encapsulation. Totally, 11.76% of patients had decreased in vision acuity. Factors including hypertensive phase, bleb encapsulation and high preoperative IOP were found to be associated with higher failure rates. Conclusions: Ahmed valve implantation is a safe and effective method for refractory glaucoma following vitrectomy.